Wonder Woman. Warbringer : the graphic novel - Simonson, Louise (DC Comics, 2020)
Diana risks exile from her land of warrior sisters to save Alia Keralis, a Warbringer--a direct descendant of the infamous Helen of Troy--as both face an army of enemies determined to either destroy or possess the Warbringer.